2015
DOI: 10.7314/apjcp.2015.16.7.2953
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induced High Expression of Thioredoxin Interacting Protein (TXNIP) in Non-small Cell Lung Cancer and its Prognostic Effect

Abstract: Although associations between thioredoxin interacting protein (TXNIP) and cancers have been recognized, the effects of TXNIP on non-small cell lung cancer (NSCLC) prognosis remained to be determined in detail. In addition, while hypoxia is a key characteristic of tumor cell growth microenvironment, the effect of hypoxia on TXNIP expression is controversial. In this study, formaldehyde fixed and paraffin embedded (FFPE) samples of 70 NSCLC patients who underwent resection between January 2010 and December 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…In addition, it has been reported that patients with high TXNIP expression demonstrated a significantly shorter progression-free survival compared with those with low TXNIP expression (31). The expression of TXNIP could also be affected by many factors including tumour environment (31). In the present study, no obvious change in thioredoxin expression was observed in response to D-allose.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In addition, it has been reported that patients with high TXNIP expression demonstrated a significantly shorter progression-free survival compared with those with low TXNIP expression (31). The expression of TXNIP could also be affected by many factors including tumour environment (31). In the present study, no obvious change in thioredoxin expression was observed in response to D-allose.…”
Section: Discussioncontrasting
confidence: 43%
“…In high-grade tumours, thioredoxin expression is diminished, suggesting loss of redox regulation in tumours with low differentiation (14). In addition, it has been reported that patients with high TXNIP expression demonstrated a significantly shorter progression-free survival compared with those with low TXNIP expression (31). The expression of TXNIP could also be affected by many factors including tumour environment (31).…”
Section: Discussionmentioning
confidence: 99%
“…No difference in splice variants, isoforms, or gene fusion were observed between the two culture conditions. Among the differentially expressed genes, we identified genes previously shown to be regulated by hypoxia, such as BNIP3 [ 26 ], SPAG4 [ 27 , 28 ], TRF2 [ 29 ] and TXNIP [ 30 ]. When genes were clustered based on biological functions, the differentially expressed genes identified were found to be involved in biological processes that are important to certain cell therapies such as: (1) chondrogenesis and cartilage metabolism; (2) inflammation and immunomodulation; (3) cellular survival, migration and proliferation; and (4) vasculogenesis and angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, expanding hBMMSCs under hypoxia in vitro rather than in atmospheric oxygen partial pressure conditions seems very intuitive and it has been proven beneficial [ 7 , 71 ]. Some of the genes identified herein have previously been described to be regulated by hypoxia, such as BNIP3 [ 26 ], SPAG4 [ 27 , 28 ], TRF2 [ 29 ] and TXNIP [ 30 ]. Stratifin (SFN) was identified for the first time as being regulated by hypoxia in hBMMSCs with a sixfold upregulation in hypoxic conditions versus atmospheric culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Yan Li and other researchers have found that hypoxia is a key feature in the tumor microenvironment. Under hypoxic conditions, the level of TXNIP in NSCLC tissues is upregulated, and high expression levels of TXNIP may be a poor prognostic indicator (114). It has been shown that using tyrosine kinase inhibitor (TKIs) to inhibit PI3K/Akt signaling in NSCLC cell lines can lead to a decrease in cell membranelocalized GLUT1, but increases in TXNIP expression in lung cancer tissues (98).…”
Section: Cancers Of the Respiratory System And Others (Table 3) Txnipmentioning
confidence: 99%